Pelatihan Instalasi Panel Surya Sebagai Penerangan dan Perawatan Ringan Motor Penggerak Kapal Nelayan - Yaser Krisnafi; Izhary Siregar; Agus Purwanto; Citra Zaskia Pratiwi; Ahmad Jibril; Iman Mawardi,; Faizin adi Nugroho (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
In an effort to improve the welfare of fishing communities, the Community Service program is an alternative in empowering the economy of fishing communities. There is a fishing village in Paciran Village, Lamongan Regency, East Java which carries out fishing activities near the coast. These fishermen experience problems with the lack of lighting when carrying out fishing activities, apart from that, fishermen also experience problems with maintenance and repair of the motors used on their boats. To overcome this problem, Community Service activities were carried out using presentation methods and training methods (workshops) regarding the installation of solar panels on fishing boats and maintenance and repair of ship motors. This activity is able to motivate fishermen to use solar panels as an energy source for lighting their ships when carrying out fishing activities as well as giving fishermen the ability to carry out maintenance and repair of ship motors independently.